Operationalizing and Researching Cosmopolitan Adult Education: Collaborative Inquiry Frameworks for Adult Educators’ International Cross-Cultural Study of Learning and Knowing - Joellen E Coryell (Adult Education Research Conference, 2018)
A discussion on cosmopolitan adult development and research in progress on the use of comparative, collaborative inquiry as a method to enhance adult educators’ cosmopolitan worldviews.
Keywords: cosmopolitan adult education; collaborative inquiry; international comparative education; qualitative research